Meningioma mimicker: non-tubercular intradural abscess - Gupta, Pankaj Kant; Garg, Sunil; Thanvi, Sharad (International Journal of Research in Medical Sciences, 2017)
Spinal subdural abscess (SSA) is a rare disease representing a loculated infection between the dura and the arachnoid. The infection may be due to haematogenous spread, iatrogenic contamination and local infection. Patient may present with varied symptoms ranging from backache to neurological deficit. Laboratory investigations will reveal increased white blood cell count (WBC) counts, raised erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), but these are non-specific. We present a case of a patient presenting as acute onset rapidly progressing paraplegia with initial Magnetic resonance imaging suggestive of meningioma or nerve sheath tumour. The patient was taken up for emergency surgery because of rapid progression of neurological deficit and intraoperatively found to have Spinal subdural abscess at D8-D9 level. There was no evidence of any tumour and the pus that was removed revealed Coagulase negative Staph aureus. The patient subsequently was given appropriate antibiotics for four weeks and showed clinical improvement on one month follow-up.